THE ROLE AND CHARACTERISTICS OF MINIMALISM IN THE FASHION WORLD - Boymatova Kamola Abduraxmon qizi; Nishonova Kamolaxon Nosirjon qizi; Rahmonberdiyeva Lobarxon Husanboy qizi; Axmadjonova Umidaxon Alxamjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Like many other styles in the fashion industry, minimalism has become an integral part of the fashion world. Due to the appearance and characteristics of minimalism based on clear rules, it is not difficult to distinguish it from other trends. This style will impress almost everyone, as it suits the tastes of many.